1999
DOI: 10.1136/gut.45.5.723
|View full text |Cite
|
Sign up to set email alerts
|

Decreased and aberrant nuclear lamin expression in gastrointestinal tract neoplasms

Abstract: Background-Altered expression of lamins A/C and B1, constituent proteins of the nuclear lamina, may occur during diVerentiation and has also been reported in primary lung cancer. Aims-To examine the expression of these proteins in gastrointestinal neoplasms. Patients-Archival human paraYn wax blocks and frozen tissue from patients undergoing surgical resection or endoscopic biopsy. Methods-Immunohistochemistry and western blotting using polyclonal antisera against A type lamins and lamin B1. Results-The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 31 publications
(7 reference statements)
6
108
0
Order By: Relevance
“…An additional study evaluating only three tissue samples has found reduced expression of lamins A, C and B1 in the non-SCLC tissue samples [185]. (17 of 17) of primary colon adenocarcinomas, and in 7 of 8 primary gastric adenocarcinoma specimens [185]. Lamin B1 expression was reduced in all the 17 colonic specimens and in 6 of 8 of the gastric specimens.…”
Section: Lamins As Biomarkers For Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…An additional study evaluating only three tissue samples has found reduced expression of lamins A, C and B1 in the non-SCLC tissue samples [185]. (17 of 17) of primary colon adenocarcinomas, and in 7 of 8 primary gastric adenocarcinoma specimens [185]. Lamin B1 expression was reduced in all the 17 colonic specimens and in 6 of 8 of the gastric specimens.…”
Section: Lamins As Biomarkers For Cancermentioning
confidence: 99%
“…The first study used immunohistochemistry techniques and found reduced expression of lamins A, C and B1 in three out of four patients with prostatic cancer [185]. The other study used immunoblot assays and reported 37 prostatic cancer patients with a significant increase in lamin B1 and no significant change in lamins A and C [193].…”
Section: Genitourinary Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…There is no overall pattern of A-type lamin expression in cancers and frequently inconsistent patterns are observed between cancer subtypes. Many studies show lamin A/C to be downregulated in tumour cells, [2][3][4] but others show positive or upregulated expression. 2,5,6 Sometimes expression levels can vary dramatically even within cancer subtypes; for example, in colorectal and basal cell carcinomas, A-type lamin expression can be positive, 4,5,7 reduced 3,4 or negative 3,4,7 in tumour tissue.…”
Section: Introductionmentioning
confidence: 99%